Humanisme dalam Tafsir Marâh Labîd Karya Nawawî al-Bantanî - Cholily, Naufal (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2016)
The article attempts to scrutinize the concept of humanism in NawawÃ® al-BantanÃ® al-JÃ¢wÃ®âs masterpiece MarÃ¢h LabÃ®d li Kashf MaâÃ¢nÃ® al-QurâÃ¢n al-MajÃ®d. When interpreting the Quranic verses on the issue of equal rights of human, NawawÃ® did not take such matters as the difference of lineage, groups and religions into accounts. He prudently emphasized that all people possess equal right and position before God. This can be clearly observed when he particularly interpreted the verses on justice in which he stressed that justice is enforced on the basis of truth. Although NawawÃ® did not explicitly mention the term of brotherhood out of in-religion brotherhood, he stated a number of terms such as akh fÃ® al-dÃ®n, akh fÃ® al-nasab, and akh fÃ® al-suhbah. He also implicitly acknowledged other kinds of brotherhood such as ukhuwwah watanÃ®yah and ukhuwwah insÃ¢nÃ®yah. In the context of humanâs freedom, NawawÃ® put great emphasis on humanâs sovereignty to choose his/her belief and religion. He stressed at the same time that each person will, however, be responsible for his/her choice along with it consequences. NawawÃ® also promulgated harmonious interrelation between Muslims and other religious adherents as long as it has nothing to do with the very core of Islamic doctrine, i.e. âaqÃ®dah.